625. PROPENSITY SCORE-MATCHED COMPARISON OF OUTCOMES BETWEEN POSTERIOR MEDIASTINAL AND RETROSTERNAL ROUTES OF RECONSTRUCTION FOLLOWING THREE-PHASE ESOPHAGECTOMY. (24th September 2022) - Wong, Claudia; Zhang, Rui Qi; Chan, Desmond; Wong, Ian; Law, Betty; Chan, Fion; Law, Simon
Abstract: The retrosternal (RS) and posterior mediastinal (PM) routes can be chosen for gastric conduit reconstruction following three-phase esophagectomy with cervical anastomosis. It is controversial if the choice of reconstruction route would affect the operative outcome. This study aims to evaluate the surgical outcome by comparing the routes of reconstruction. Between 2002 and 2019, patients who underwent esophagectomy with cervical anastomosis and gastric conduit reconstruction via the retrosternal (RS) or posterior mediastinal (PM) route for esophageal squamous cell cancer were included. Clinicopathological data were analyzed from a prospectively managed database. Postoperative morbidity and mortality rates, presence of recurrent tumor invasion of the conduit and overall survival were compared between the two groups. Further analyses were made after propensity score matching (PSM). There were 89 patients in the RS and 266 in PM groups. R0 resection rates were 47.2% and 89.1% in the RS and PM groups, respectively (p<0.01). Anastomotic leak occurred more frequently in RS group at 16.9% vs. 6.8%, (p=0.007) while cardiac complications were fewer; 19% vs. 32%, (p=0.02). 90-day mortality rates were <4% in both groups. Median survival was 20 and 64 months in RS and PM groups respectively (p<0.01). PSM yielded 60 patients in each group. Postoperative morbidities, and survival, were similar. Mediastinal tumor recurrences infiltrated the gastric conduit only in the PM group in 6.8% of patients. When corrected for selection biases, RS and PM routes did not differ in post-operative morbidity and mortality rates. Placing the gastric conduit in the RS route could avoid invasion by mediastinal tumor recurrence. RS is the preferred route of reconstruction after a three-phase esophagectomy.